Enhancing Geospatial Preparedness for Disaster Management through the work of development organisations - Hernaiz, Roberto San Martin (2020)
A thesis submitted in partial fulfillment of the requirements for the degree of Doctor in Information Management, specialization in Geographic Information Systems